Analysis of combined extrusion micro coining process to manufacture microstructured tappets - Zahner, Michael; Merklein, Marion (Procedia Manufacturing, 2018)
In times of enhanced functional integration of machine elements the combination of forming processes offers an opportunity to increase the efficiency of the manufacturing process. Due to mutual interactions combining different forming operations a comprehensive analysis of the processes is necessary especially regarding micro forming processes. Within this study a combined extrusion micro coining process to manufacture microstructured tappets was investigated. The results reveal that the achieved homogeneity on tappet surface is mainly influenced by the microstructure layout applied on the tool components, due to locally widely varying material flow in the coining region.
LFT Import::2019-07-29 (2334)
Keywords: Combined forming process; Geometrical accuracy; Micro Coining; Microstructures; Tribology